Analisis Stres dan Kualitas Tidur Terkait dengan Tingkat Gula Darah pada Pasien Diabetes Mellitus Tipe 2 di Rumah Sakit Islam Sultan Agung Semarang - Putri Diana Damayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aimed to analyze the relationship between stress levels and sleep quality with random blood glucose (RBG) among patients with Type 2 Diabetes Mellitus (DM-2) at RSI Sultan Agung Semarang. A cross-sectional design was applied with 92 respondents selected through purposive sampling. Data on stress levels were measured using a standardized questionnaire, while sleep quality was assessed through self-reported indicators. Blood glucose levels were collected based on clinical laboratory results. Statistical analysis showed a significant correlation between stress and RBG (p = 0.011; r = 0.586), indicating that higher stress levels were associated with elevated glucose values. A stronger relationship was identified between sleep quality and RBG (p = 0.0001; r = 0.629), suggesting that poor sleep quality substantially increases the risk of hyperglycemia. These findings highlight the dual influence of psychological and behavioral factors on glycemic regulation. Physiological mechanisms, including hypothalamic-pituitary-adrenal axis activation and reduced insulin sensitivity, may explain the association between stress, sleep, and glucose dysregulation. The results underscore the importance of incorporating psychological assessment, stress management strategies, and sleep hygiene education into diabetes care. An integrated approach may enhance glucose control and contribute to better long-term outcomes for patients with DM-2.